(untitled) - Fekete, Sandra (Hoboken, NJ., 2003)
What you learn about your company will help you strengthen your brand, differentiate yourself from the competition, and fix problematic areas. Companies Are People, Too is a revolutionary program that helps you as a business leader get to know the core personality of your company in order to take your performance to a higher level. Equipped with a sense of who your company is, you can ease organizational change, attract and retain employees, articulate company-wide values, and send consistent messages.
Keywords: Organizational behavior,Corporate culture